STUDI ETNOFARMASI TUMBUHAN BERKHASIAT OBAT PADA SUKU KAILI LEDO DI KABUPATEN SIGI, PROVINSI SULAWESI TENGAH - Ian Dianto; Syariful Anam; Akhmad Khumaidi (Universitas Tadulako, 2015)
Ethnomedicinal study on LedoKaili tribe has been conducted from January to April 2015 in Sigi Regency, Central Sulawesi. This study aims to know and to inventory the various species of plants, their parts, and ways of utilization used to treat any types of disease and how the by the tribe. This research is descriptive using qualitative methods and snowball sampling technique through open-ended interviews to 10 informants by using questionnaire. Based on the study results, plants used as medicine were known as many as 86 species coming from 37 familia in which four species have notbeen identified yet. The most widely used plants are from familia Zingiberaceae (8 species). Plant parts used include leaf, stem, fruit, root, rhizome, tuber, herb, bark, sap, and flower. Leafisthe part of the plant used with the highest percentage (53%). Local people use medicinal plants for purposes of chronic, infectious, and non-infectious diseases. Besides being able to treat people's illnesses,the plants were also used for body health care as well as dietary supplements. Ways of processing medicinal plants is done by boiling, crushing, squeezing, shredding and soaking. The most widely is boiled with percentage of 60%. As for how to use medicinal plants, the people use them in ways of drinking, eating, rubbing, dropping, and tapping/attaching. Drinking is the most usual way to use them with a percentage of 74%